PENINGKATAN KEMAMPUAN MENULIS TEGAK BERSAMBUNG DENGAN METODE LATIHAN SISWA KELAS II SD NEGERI 016 KECAMATAN PEKANBARU KOTA KOTA PEKANBARU - Marwati Marwati (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2017)
The background of this study is the low ability students in writing upright continued. This is evidenced by the acquisition of student learning outcomes about the erect continued writing only obtained a score of 65.83. It is caused by: (a) the lack of training provided to student teachers; (b) teachers was minimal provide supporting books; (c) the lack of interest of the students to receive materials continued upright posts; (d) the teacher has not found the right technique or method in presenting the material. Based on this, researchers applied the training methods with the aim of improving writing skills upright continued. This research is a class act who performed at SD Negeri 16 Kecamatan Pekanbaru. The results of this study indicate that the ability of students has increased, this is evidenced by: (a) in the first cycle of activity for teachers to get a score of 39 (65.00%), the second cycle teachers' scores obtained was 51 (85.00%). While the student activity data in the first cycle obtained a score of 39 (65.00%), the second cycle score obtained by the students was 51 (85.00%); and (b) in the first cycle the average ability of students to write concatenated upright is 72.5 with enough categories. In the second cycle the average ability of students to write upright continued to rise to 81.5 in both categories.